Makna Pesan Politik pada Foto Akun Instagram Anies Baswedan - Gagas Tri Anggoro; Suyanto; Muchid (Unitri Press, 2022)
This study was motivated by the summons of Anies Baswedan by the authorities due to the permission of the prophet's birthday, demonstrations due to omnibus law, and the decline in Indonesia's democracy index, resulting in an Instagram photo of Anies Baswedan reading the book